Long‐Term Oral Bisphosphonate Therapy and Fractures in Older Women: The Women's Health Initiative. Issue 9 (29th May 2017) - Drieling, Rebecca L.; LaCroix, Andrea Z.; Beresford, Shirley A. A.; Boudreau, Denise M.; Kooperberg, Charles; Chlebowski, Rowan T.; Ko, Marcia G.; Heckbert, Susan R.
Abstract : Objectives: To examine the association between long‐term bisphosphonate use and fracture in older women at high risk of fracture. Design: Retrospective cohort. Setting: Women's Health Initiative. Participants: Older women who reported at least 2 years of bisphosphonate use in 2008–09 (N = 5, 120). Measurements: Exposure data were from a current medications inventory. Outcomes (hip, clinical vertebral, wrist or forearm, any clinical fracture) were ascertained annually. Using multivariate Cox proportional hazards models, the association between duration of bisphosphonate use (3–5, 6–9, 10–13 years) and fracture was estimated, using 2 years as the referent group. Results: On average participants were 80 years old and were followed for 3.7 ± 1.2 years. There were 127 hip, 159 wrist or forearm, 235 clinical vertebral, and 1, 313 clinical fractures. In multivariate‐adjusted analysis, 10 to 13 years of bisphosphonate use was associated with higher risk of any clinical fracture than 2 years of use (hazard ratio (HR) = 1.29, 95% confidence interval (CI) = 1.07–1.57). This association persisted in analyses limited to women with a prior fracture (HR = 1.30, 95% CI = 1.01–1.67) and women with no history of cancer (HR = 1.36, 95% CI = 1.10–1.68). The association of 10 to 13 years of use, compared with 2 years of use, was not statistically significant for hip (HR = 1.66, 95% CI = 0.81–3.40), clinical vertebral (HR = 1.65, 95% CI = 0.99–2.76), or wrist fracture (HR = 1.16, 95% CI = 0.67–2.00). Conclusion: In older women at high risk of fracture, 10 to 13 years of bisphosphonate use was associated with higher risk of any clinical fracture than 2 years of use. These results add to concerns about the benefit of very long‐term bisphosphonate use.